Generation and detection of incoherent hypersonic vibrations using superconducting tunnel junctions - ALEKSIEJUK, Mikołaj; DOBRZAŃSKI, Mieczysław M.; LARECKI, Wiesław (Archives of Acoustics, 1980)
The investigations of superconducting tunnel junctions as phonon generators and detectors are reported. Theoretical predictions and the published results of the experimental research on such devices are briefly reviewed. The experimental results of the investigations of the current-voltage characteristics of fabricated tin tunnel junctions are presented and discussed, and then the measured current-signal transmission characteristics of pairs of identical tunnel junctions deposited on the corundum sample are analyzed and interpreted. The results obtained are compared with the results of similar investigations reported in the literature.